2008
DOI: 10.1111/j.1742-4658.2008.06564.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the arginine/serine dipeptide‐rich motif of the severe acute respiratory syndrome coronavirus nucleocapsid protein modulates its multimerization, translation inhibitory activity and cellular localization

Abstract: Coronavirus nucleocapsid protein is abundant in infected cells and participates in viral RNA replication and transcription. The central domain of the nucleocapsid protein contains several arginine/serine (RS) dipeptides, the biological significance of which has not been well investigated. In the present study, we demonstrate that the severe acute respiratory syndrome coronavirus nucleocapsid protein is phosphorylated primarily within the RS‐rich region in cells and by SR protein kinase 1 in vitro. The nucleoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
243
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(247 citation statements)
references
References 51 publications
4
243
0
Order By: Relevance
“…1B, black bold (24) demonstrated this region as the major phosphorylation region for SCoV N in HEK293 cells. To test this, we constructed a SR region-deleted N construct (⌬SR-N, deletion of amino acids 178 -213), expressed the mutant protein, and immunoprecipitated it from 293T cells for analysis.…”
Section: The N Protein Of Scov Is Phosphorylated In Veroe6 and 293tmentioning
confidence: 99%
See 1 more Smart Citation
“…1B, black bold (24) demonstrated this region as the major phosphorylation region for SCoV N in HEK293 cells. To test this, we constructed a SR region-deleted N construct (⌬SR-N, deletion of amino acids 178 -213), expressed the mutant protein, and immunoprecipitated it from 293T cells for analysis.…”
Section: The N Protein Of Scov Is Phosphorylated In Veroe6 and 293tmentioning
confidence: 99%
“…The phosphorylated SCoV N was recently shown to translocate from the nucleus to the cytoplasm by binding with the 14-3-3 protein, as a mechanism for phosphorylation-dependent nucleocytoplasmic shuttling (18). Recently, Peng et al (24) reported that phosphorylation of SCoV N at the SR-rich motif could modulate its translation inhibitory activity and also its multimerization activity. Based on these observations, the phosphorylation of N protein has long been proposed to participate in regulating viral replication, but currently there is a lack of conclusive evidence supporting its critical involvement.…”
mentioning
confidence: 99%
“…All three IDRs of coronaviral N protein can modulate the RNA-binding and oligomerization properties of NTD and CTD, respectively [6]. In addition, the LKR of the N protein with Ser-Arg-rich sequences has also been shown to contain an RNA-binding region and putative phosphorylation sites that might regulate N protein functions [7,8] and N-M interaction. No existing data supports the presence of a long-lived SARS-CoV N oligomer or intermediate in solution and the SARS-CoV genomic ssRNA by itself is unlikely to exist as a helix of the length observed in cryo-EM.…”
mentioning
confidence: 99%
“…SARS-CoV NC protein was phosphorylated at several serine residues in a serine-arginine rich motif in the central domain required for oligomerization of the NC protein and translocation of the NC to the nucleus. 72,[77][78][79] Phosphorylation affects the interaction between NC subunits and regulates the ability of NC to suppress translation. 78 Glycogen synthase kinase 3, one of the kinases that phosphorylate NC protein, can be inhibited to suppress the replication of SARS-CoV.…”
mentioning
confidence: 99%
“…72,[77][78][79] Phosphorylation affects the interaction between NC subunits and regulates the ability of NC to suppress translation. 78 Glycogen synthase kinase 3, one of the kinases that phosphorylate NC protein, can be inhibited to suppress the replication of SARS-CoV. 80 Rabies virus (RV) is a (−)-strand ssRNA enveloped virus and a member of the family Rhabdoviridae.…”
mentioning
confidence: 99%